Structural valve deterioration is primarily caused by cyclic fatigue but not immune rejection - Kostyunin, Alexander E.; Glushkova, Tatiana V.; Ovcharenko, Evgeny A.; Onischenko, Pavel S.; Klyshnikov, Kirill Yu.; Akentieva, Tatiana N.; Bogdanov, Leo A.; Koshelev, Vladislav A.; Stasev, Alexander N.; Khromov, Anton A.; Kutikhin, Anton G. (Frontiers in Immunology, 2025)
IntroductionCurrently, chronic immune rejection of bioprosthetic heart valves (BHVs) is considered among the key players in the development of structural valve degeneration (SVD). However, the relative contribution of leukocyte infiltration and cyclic mechanical loading into the SVD in bioprosthetic mitral valves (BMVs) and bioprosthetic tricuspid valves (BTVs, experiencing lower hemodynamic load due to the right heart’s pressure environment) remains unclear.MethodsHere we performed an investigation of BMVs and BTVs which have been pairwise-excised from 4 patients during the BHV replacement because of BMV failure. The amount of valvular calcification was measured by multislice computed tomography and quantified using Pydicom script. Immune cell infiltration and lipid deposition in sectioned leaflets were evaluated by hematoxylin and eosin and Oil Red O staining, respectively; the semi-quantitative analysis of whole slide images was conducted by QuPath and Fiji software. In addition, we conducted an ultrastructural examination of BHVs by backscattered scanning electron microscopy after epoxy resin embedding (EM-BSEM technique).Results and discussionAll BMVs had a significant extent of lipid deposition, hemorrhages, and tears, which eventually led to its mechanical incompetence. Strikingly, BMVs had less amount of immune cell infiltration as compared with BTVs. These results indicate that mechanical fatigue prevails over immune cell infiltration in driving the development of SVD.